EXHUMED CONFLICT IN EAST AFRICA: CAUSES AND IMPLICATIONS OF ETHNIC CONFLICT IN BURUNDI. - Abdallah, Mpawenimana Saidi; Adam Andani, Mohammed; Bougangue, Bassoumah (International Journal of Advance Research, 2017)
The world-wide conflicts around ethnic identities remind that communal identities can be a potent force in contemporary societies. Ethnicity is more central to the political process of many African countries including Burundi as the oppressed population struggle for their share of the national cake. As a result, ethnic conflict gives rise to unstable domestic system as it takes place within national borders. This research employed qualitative research method so data collection was dependent on primary sources in addition to the researcher‟s know-how. The complementary secondary data was through the internet and library materials to help the understanding of the matter at hand. The paper examined the causes and implications of ethnic conflict in Burundi. It is done with the hope that trends that lead to conflict and those that lead to cooperation can be identified. The study found lack of equity and justice, high illiteracy levels and an external threat as factors which fun ethnic conflict in the country. Besides, the education system by ethnic and regional entities has created a gap between state institutions and the population resulting in vicious cycle of frustration in which ethnic conflict triumph. Ethnic conflicts can thus be interpreted as struggles for the collective goods of the country.